2021
DOI: 10.3390/ijms22094560
|View full text |Cite
|
Sign up to set email alerts
|

BMP Signaling Interferes with Optic Chiasm Formation and Retinal Ganglion Cell Pathfinding in Zebrafish

Abstract: Decussation of axonal tracts is an important hallmark of vertebrate neuroanatomy resulting in one brain hemisphere controlling the contralateral side of the body and also computing the sensory information originating from that respective side. Here, we show that BMP interferes with optic chiasm formation and RGC pathfinding in zebrafish. Experimental induction of BMP4 at 15 hpf results in a complete ipsilateral projection of RGC axons and failure of commissural connections of the forebrain, in part as the resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 66 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Moreover, using heptanol, a well-known gap junction blocker, the authors showed that calcium wave propagation, but not initiation, required fully functional gap junctions. Knickmeyer et al [10] investigated the role of bone morphogenetic protein (BMP) signaling, especially BMP4, in optic nerve pathfinding using a transgenic line encoding the zebrafish bmp4 gene under the heat-inducible hsp70 promoter, allowing precise overexpression timing. The authors thereby showed that BMP signaling was dynamic and overexpression of bmp4 impaired both the elongation of optic nerves and their crossing at the optic chiasm, suggesting for the first time a requirement for BMP signaling in retinal ganglion cell projections to the brain.…”
mentioning
confidence: 99%
“…Moreover, using heptanol, a well-known gap junction blocker, the authors showed that calcium wave propagation, but not initiation, required fully functional gap junctions. Knickmeyer et al [10] investigated the role of bone morphogenetic protein (BMP) signaling, especially BMP4, in optic nerve pathfinding using a transgenic line encoding the zebrafish bmp4 gene under the heat-inducible hsp70 promoter, allowing precise overexpression timing. The authors thereby showed that BMP signaling was dynamic and overexpression of bmp4 impaired both the elongation of optic nerves and their crossing at the optic chiasm, suggesting for the first time a requirement for BMP signaling in retinal ganglion cell projections to the brain.…”
mentioning
confidence: 99%